SYNTHESIS AND ANTIFUNGAL ACTIVITY SCREENING OF SOME NOVEL 7-SUBSTITUTED -2-HYDROXY-QUINOLINE SCHIFF BASES - Kumar, M R Pradeep (Journal of Applied Pharmaceutical Research, 2016)
With an objective of synthesizing some novel, potent and broad spectrum antifungal activity having compounds, here some novel quinoline derivatives are reported. Initially 7-substituted-2-cholro-3-formylquinolines were prepared using well known Vilsemeir-Hack reagent method. These on microwave irradiation with 4M HCl yielded 7-substituted-2-hydroxy quinoline-3-carbaldehydes I(a, b), which on further treatment with different substituted hydrazides yielded the novel Schiff bases of quinoline II(a-f). The structure of all newly synthesized compounds was confirmed by spectral study such as IR, 1H NMR, 13C NMR and mass spectroscopy. All the synthesized compounds were screened for in-vitro antifungal activity by two fold serial dilution method using fluconazole as the standard drug. Compounds II a, II b and II d showed significant antioxidant activity.